Pendekatan Intervensi Keperawatan Jiwa untuk Mengurangi Gejala Depresi pada Lansia Demensia di Indonesia dan di Jepang : Literature Review - Firda Anilatul Wafa; Laura Khattrine Noviyanti; Titik Suerni (The Journal General Health and Pharmaceutical Sciences Research, 2024)
The definition of Health is a complete physical and mental condition, free of disease or disability. Feelings of uselessness, sadness, insomnia, stress, depression, anxiety, delirium, and dementia are signs of psychological regression in the elderly. Health care for depressed parents with dementia requires non-pharmacological care. Objective: This research analyzes the effects of reminiscence therapy, Brain Gym, and music therapy to relieve elderly people suffering from dementia and depression. This literature review research took the published articles from 2014 to 2024 on Google Scholar and Pubmed. The researchers collected relevant data or sources based on the keywords. The results found both in Indonesia and Japan, non-pharmacological care interventions like reminiscence therapy had a significant impact. However, the Brain Gym intervention group and music therapy performed in Japan had no significant impact on relieving depression or improving the cognitive function of dementia patients. Conclusion: Reminiscence therapy succeeded in relieving cognitive function in parents suffering from dementia in Indonesia and Japan. Therefore, reminiscence therapy is suggested to be applied in Japan.